Psychometric properties of the Dutch SAQOL-39NL in a generic stroke population. Issue 2 (17th February 2019) - Van Ewijk, Lizet; Ter Wal, Nicole; Okx, Gisella; Goossens, Paulien; Groeneveld, Iris
ABSTRACT: Background: The psychometric properties of the Dutch version of the Stroke and Aphasia Quality Of Life-scale (SAQOL-39NL) have previously been assessed for people with aphasia after stroke, but not yet for stroke survivors without aphasia. Objective: The objective is to evaluate the psychometric properties of the SAQOL-39NL in a stroke sample with and without aphasia. Methods : The SAQOL-39NL was administered to survivors of stroke ( N = 141) who received rehabilitation in specialized rehabilitation facilities, 3 and 6 months after the start of rehabilitation. Acceptability was explored by assessing floor and ceiling effects and missing items. For internal consistency, Cronbach's alpha and item-total correlations were computed. For internal validity, intercorrelations between domains, and between domains and total score, were assessed. Convergent validity was evaluated by correlation with EuroQoL-5D scores. Responsiveness to change was investigated using d′ and SRM-scores. Results : Mean age was 60.4 years (SD = 11.1), 62.4% were male. Mean total SAQOL-39NLg score was 3.94 (SD = 0.68, scale 1–5). No floor or ceiling effects and 2.4% missing data were found. Internal consistency was excellent (Cronbach's alpha = 0.96). Intercorrelations between domains and total scale were moderate to excellent ( r = 0.57–0.88). Intercorrelations between domains were low to moderate ( r = 0.22–0.63). The correlation with the EQ-5D was moderate ( r = 0.57). Only small changes in SAQOL-39NLg scores were found between 3 and 6 months. Conclusions: These data provide further evidence for the acceptability, internal consistency, and initial promising data on validity of the SAQOL-39NLg. Further research on structural validity and responsiveness to change is needed.